ANALISIS KOMUNIKASI KEBIJAKAN MARITIM INDONESIA - Hary, Martinus (Sintesa, 2024)
This article aims to discuss maritime policy communication strategies in Indonesia with a focus on disseminating information to stakeholders. Maritime policy communication is considered important to ensure understanding, support and active participation in the implementation of maritime policy. Through a descriptive qualitative approach, this research identifies internal and external factors that influence maritime policy communication, including culture, leadership, human resources, organizational structure, integration of government institutions, and global dynamics. This research also highlights the role of government in maritime policy communication, emphasizing the importance of transparency, public participation, and the use of information technology. Obstacles such as the complexity of maritime issues, limited resources, differences in stakeholder understanding, and the influence of the media and public opinion are also discussed. In facing this challenge, researchers are interested in researching Maritime policy communication analysis: stakeholder engagement strategies in Indonesia where researchers focus on establishing clear communication objectives, identifying stakeholders, selecting appropriate media, and managing diverse understandings and interests. In conclusion, effective maritime policy communication is needed to maximize Indonesia’s maritime potential and achieve sustainable maritime sector development goals. The research results show that there is complexity of maritime issues, limited resources, and there are differences in understanding and interests of stakeholders and often there is a choice of appropriate communication media. These limitations continue to be improved for the good of the maritime world in Indonesia. Keywords: Policy Communication, Maritime, Stakeholders, State, Development.